Cell cycle-dependent changes in H3K56ac in human cells - Stejskal, Stanislav; Stepka, Karel; Tesarova, Lenka; Stejskal, Karel; Matejkova, Martina; Simara, Pavel; Zdrahal, Zbynek; Koutna, Irena (Cell Cycle, 2015)
The incorporation of histone H3 with an acetylated lysine 56 (H3K56ac) into the nucleosome is important for chromatin remodeling and serves as a marker of new nucleosomes during DNA replication and repair in yeast. However, in human cells, the level of H3K56ac is greatly reduced, and its role during the cell cycle is controversial. Our aim was to determine the potential of H3K56ac to regulate cell cycle progression in different human cell lines. A significant increase in the number of H3K56ac foci, but not in H3K56ac protein levels, was observed during the S and G2 phases in cancer cell lines, but was not observed in embryonic stem cell lines. Despite this increase, the H3K56ac signal was not present in late replication chromatin, and H3K56ac protein levels did not decrease after the inhibition of DNA replication. H3K56ac was not tightly associated with the chromatin and was primarily localized to active chromatin regions. Our results support the role of H3K56ac in transcriptionally active chromatin areas but do not confirm H3K56ac as a marker of newly synthetized nucleosomes in DNA replication.
Keywords: HL-60 buňky; Saccharomyces cerevisiae Proteins; Cell Cycle; G2 fáze; Chromatin; Saccharomyces cerevisiae; lidé; S Phase; replikace DNA; HL-60 Cells; hmotnostní spektrometrie; buněčný cyklus; G2 Phase; chromatin; nukleozomy; Mass Spectrometry; histony; Histones; S fáze; Saccharomyces cerevisiae - proteiny; DNA Replication; Nucleosomes; Humans